'Preparing ourselves to become an international organization': Thailand Tobacco Monopoly's regional and global strategies. Issue 3 (4th March 2017) - MacKenzie, Ross; Ross, Hana; Lee, Kelley
ABSTRACT: The Thailand Tobacco Monopoly (TTM) controlled the country's tobacco industry from its formation in the 1940s, until the government dropped restrictions on imported cigarettes in the late 1980s in response to pressure from the United States. The TTM has since competed with transnational tobacco companies (TTCs) in a semi-monopoly market in which TTCs have steadily increased their market share. Coupled with a decline in national smoking prevalence, the result of Thailand's stringent tobacco control agenda, the TTM now accounts for a diminishing share of a contracting market. In response, the monopoly has looked to regional trade liberalisation, and proximity to markets with some of the world's highest smoking rates to expand its operations. Expansion strategies have gone largely unrealised however, and the TTM effectively remains a domestic operation. Using TTM publications, market and trade reports, industry publications, tobacco industry documents and other resources, this paper analyses TTM expansion strategies, and the limited extent to which they have been achieved. This inability to expand its operations has left the monopoly potentially vulnerable to global strategies of its transnational competitors. This article is part of the special issue 'The Emergence of Asian Tobacco Companies: Implications for Global Health Governance'.